A legal analysis of the application of corporate governance principles in Musina Local Municipality - Mkhabele, Cynthia Jose Merrill Masingita (University of Limpopo (Turfloop Campus), 2014)
This mini-dissertation discusses the application of the principles of corporate governance in the Musina Local Municipality. It further discusses the legislative framework and the institutions of government which are responsible for the effective implementation of corporate governance in the local government sphere. It further discusses the challenges faced by Musina Local Municipality which are ranging from fraud and corruption and poor financial management and this result in poor service delivery.
Thesis (LLM. (Labour Law)) --University of Limpopo, 2014
Keywords: Corporate Governance; Musina Local Municipality; Legal Analysis; 346.0662; Corporate governance - Law and legislation; Corporate governance - South Afirca; Musina Local Municipality (Limpopo)